“Raising Enterprises to Evangelize and Relief”: A New Exploration of the “Industrial Missionary Work” of Rev. William N. Brewster who evangelized in Hinghwa Fujian around 1900 - TANG, Shoukang (Journal of Research for Christianity in China (JRCC), 2025)
During the late Qing Dynasty, with the opening of five ports for trade, Protestant missionaries flocked to China. Among them, the American Methodist Episcopal Church’s missionary, William N. Brewster, carried out his preaching activities in Hinghwa city, Fujian Province with the strategy of “Industrial Missionary Work”. However, at the same time, other missionaries opposed his “Industrial Missionary Work”, believing that it would lead to a secularization tendency. So, does Brewster’s method really work? What is its theological basis? And what are the actual effects and what kind of influence does it have? Based on these questions, this paper taking the historical background of that time as the starting point, re-examines and analyzes this strategy’s origin, characteristics, and the role it played in the development of Hinghwa indigenous church, aim to deepen the understanding of William N. Brewster and the Methodist Church. At the same time enrich the research on the history of Christian missionary work and the regional history of Christianity in Fujian.
Keywords: William N. Brewster, Industrial Missionary Work, Methodist Episcopal Church, Hinghwa Fujian